2013
DOI: 10.1158/1535-7163.mct-12-0966
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib Overcomes Irinotecan Resistance in Colorectal Cancer by Inhibiting the ABCG2 Drug-Efflux Pump

Abstract: Despite recent advances in the treatment of colorectal cancer (CRC), tumor resistance is a frequent cause of chemotherapy failure. Therefore, new treatment options are needed to improve survival of patients with irinotecan-refractory CRCs, particularly those bearing KRAS mutations that preclude the use of anti-EGFR therapies. In this study, we investigated whether sorafenib could reverse irinotecan resistance, thereby enhancing the therapeutic efficacy of routinely used irinotecan-based chemotherapy. We used b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 41 publications
4
36
0
Order By: Relevance
“…Previous experimental studies indicated the potential of this multityrosine kinase inhibitor to augment the antitumour efficacy of irinotecan in hepatocellular carcinoma cells20 21 and to overcome irinotecan resistance in colorectal cancer cells in mice 27. Furthermore, the Web-based register ClinicalTrials.gov (https://clinicaltrials.gov) specifies ongoing and recently closed studies, respectively, analysing the safety and efficacy of a combined therapy with irinotecan and sorafenib versus irinotecan or sorafenib monotherapy in patients with colorectal neoplasms or paediatric solid tumours.…”
Section: Discussionmentioning
confidence: 99%
“…Previous experimental studies indicated the potential of this multityrosine kinase inhibitor to augment the antitumour efficacy of irinotecan in hepatocellular carcinoma cells20 21 and to overcome irinotecan resistance in colorectal cancer cells in mice 27. Furthermore, the Web-based register ClinicalTrials.gov (https://clinicaltrials.gov) specifies ongoing and recently closed studies, respectively, analysing the safety and efficacy of a combined therapy with irinotecan and sorafenib versus irinotecan or sorafenib monotherapy in patients with colorectal neoplasms or paediatric solid tumours.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that multi-tyrosine kinase inhibitors such as sorafenib may also reverse irinotecan resistance (Mross et al , 2007; Azad et al , 2013). Indeed, sorafenib has been identified both in vitro and in vivo as an inhibitor of the drug-efflux pump ABCG2, favouring irinotecan intracellular accumulation thereby enhancing its toxicity (Mazard et al , 2013). This chemosensitizing property previously described by Wei et al (2012) has also been ascribed to the inhibition of the irinotecan-mediated p38 and ERK activation (Mazard et al , 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, only a Phase I trial showed the feasibility of combining a weekly schedule of irinotecan 125 mg m − 2 (D1,8,15,22 D1=D42) and a fixed dose of sorafenib 400 mg twice daily in 34 patients with solid tumours (23 of whom had colorectal cancer) (Mross et al , 2007). However, preclinical promising results had already been gathered on the synergistic effect of this combination particularly in KRAS -mutated tumours (personal communication at the time) and were recently published (Mazard et al , 2013). …”
mentioning
confidence: 99%
“…Mutations of the EGFR are correlated with tumor proliferation. Inhibition of EGFR by smallmolecule inhibitors, such as gefitinib (151), pelitinib (152), neratinib (153), vandetanib (154), and telatinib (155), is therefore a promising therapeutic option. 2 Gefitinib (151, "Iressa," ZD1839, Fig.…”
Section: Epidermal Growth Factor Receptor (Egfr) Inhibitorsmentioning
confidence: 99%